Motivasi Ibu Tentang Toilet Training Pada Anak Usia I-3 Tahun Di Wilayah Kerja Posyandu Dahlia Puskesmas Campurejo Kota Kediri - Hengki Irawan; Irma Dewi L (coba, 2013)
Toilet Training on child constitutes an effort to see child to be able to controls deep poo and pee. So required by task for toilet training. Toilet Training is very important for the child's independence and psychological. So desperately needed readiness Mother, How the implementation and the role of mother in teaching Children Toilet Training. The purpose of this study was to determine maternal motivation in making toilet training in children aged 1-3 years in the working area of Dahlia IHC Health Center Campurejo Kediri.The design of this study using a descriptive design,this research in the working area of Dahlia IHC Health Center Campurejo Kediri.Its research subject is all Mother that have age child 1-3 years in IHC Dahlia June Dahlia 2011 as much 25 respondents (Total sampling). Collecting data with questionnaires and interviews. Its research variable is motivate mother in does toilet training. Data processing utilizes kualitatif's scale passes through editing, coding, tabulating, and scoring. so research measure is divided as tall motivation, motivation be and low motivation.Result respondenting to figure 6 respondents (24%) having motivation less, 5 respondents (20%) having motivation be and a considerable part which is 14 respondents (56%) having tall motivation.So gets to be concluded by tall mother motivation to do toilet training caused total families deep child which more than one more make to have more experience ripe,mother work a large part housewife so mother time to do toilet training more intensive.The advice given is expected given the huge benefits to the mother and child about toilet training. Mother ought to applies toilet training on child and toilet training my mother taught to children early on. Keywords: motivation, Mother, Toilet Training